Analisis Strategi Promosi Dalam Meningkatkan Penjualan Produk Pada Resto Dan Pusat Oleh-Oleh Putra Nirwana Magetan Di Era Pandemi Covid - Deyana Ayu Suciana; Erwin Syahputra (Universitas 45 Surabaya, 2023)
In this era of globalization, Indonesia faces strict industrial competition, especially in an increasingly open and independent culinary industry. The Son of Nirwana is the largest rest and by-by center that has the most complete facilities in the Magetan area. Strategic action needs to be taken by managers to always be innovative, understand market trends and adaptive in order to survive the Covid 19 pandemic era. The study aims to analyze the Promotional Strategies on Resto and the Nirwana Son Magetan Center during the Covid pandemic period in increasing product sales. The study used descriptive qualitative methods and triangulation data validity analysis. Data collection is done through observations, interviews, and documentation. The results of the analysis obtained in this study indicate that Resto and the Center for the Promotion of the Son of Nirwana Magetan implemented several promotional mixtures, namely: advertising, sales promotion through the provision of product samples, discounted prices and free shipping costs, public relations, individual sales and direct marketing, In addition, the promotion carried out by Resto & the Center by the Son Of Nirvana Magetan through the use of promotional media such as the internet (social media) through instagram and the group of whatsapp tourists (table top) so that resto and center by the son of Niriwana can survive in the pandemic era.